Implementation of the Flipped Classroom in Learning Sound Wave toward Students' Learning Interest - Hasanah, Miswatul; Septian, Ilham (Jurnal Pendidikan MIPA, 2023)
This study aims to see the influence of the Flipped Classroom learning model on student learning interests. Samples were taken by purposive sampling technique with samples of students of grade XI IPA1 and XI IPA2 SMAN 9 Banda Aceh. The method used quasi-experiment with the design of The Nonequivalent Control Group Design. The instrument used is a questionnaire using the Likert scale to measure students' interest in learning. The results of the study showed that there was a difference in increased interest in learning between students who taught with the flipped classroom model and classes without the flipped classroom model. Testing the hypothesis of increased interest in learning has tcount = 4.108 > ttable = 2.306 with a two-sided significance value (Sig. 2-tailed) greater than α = 0.05 which is 0.003, meaning that there is a significant difference, then Ha is accepted and H0 is rejected. Keywords: flipped classroom, interest in learning, physics education. DOI: http://dx.doi.org/10.23960/jpmipa/v24i2.pp505-515